ABCC4 Variants Modify Susceptibility to Kawasaki Disease in a Southern Chinese Population. (30th September 2018) - Che, Di; Pi, Lei; Fang, Zhenzhen; Xu, Yufen; Cai, Minmin; Fu, Lanyan; Zhou, Huazhong; Zhang, Li; Gu, Xiaoqiong
Abstract : A previous family-based linkage study revealed that Kawasaki disease (KD) was associated with variations of the ATP-binding cassette subfamily C member 4 (ABCC4) gene in most European populations. However, significant differences exist among ethnic populations in European and Chinese subjects; therefore, whether ABCC4 variants indicate susceptibility to KD in Chinese children is unclear. The purpose of this research was to evaluate correlations between ABCC4 gene polymorphisms and susceptibility to KD in a Southern Chinese population. We genotyped six polymorphisms (rs7986087, rs868853, rs3765534, rs1751034, rs3742106, and rs9561778) in 775 KD patients and 774 healthy controls. Ninety-five percent confidence intervals (95% CIs) and odds ratios (ORs) were used to assess the strength of each association. We found that the rs7986087 T variant genotype was associated with significantly higher susceptibility to KD (adjusted OR = 1.30, 95% CI = 1.05–1.60 for rs7986087 CT/TT). However, the rs868853 T variant genotype was associated with significantly lower susceptibility to KD (adjusted OR = 0.74, 95% CI = 0.59–0.92 for rs868853 CT/CC). Compared with the patients with 0–4 ABCC4 risk genotypes, the patients with 5-6 ABCC4 risk genotypes had a significantly increased risk of KD (adjusted OR = 1.63, 95% CI = 1.07–2.47), and this risk was more significant in the subgroups of females, subjects aged 12–60 months, and individuals with coronary artery lesions. These results indicate that specific single-nucleotide polymorphisms in the ABCC4 gene may increase susceptibility to KD in a Southern Chinese population.